Contextualising arguments on deficiency of women’s intelligence and religion: analytical study on the prophetic traditions - Nur Saadah Hamisan@Khair, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Despite the increasing numbers of women and being majority of the world’s population compared to men, women were still found to be discriminated and oppressed due to many reasons. Feminists claims that religious texts were to be blamed for spreading misogynistic contents, and male’s interpretations became one of the main sources of conflict with regards to the women’s issues. One of the statements which can be found in the Hadith literature that had been debated among them is “women are deficient in intelligence and religion”. This paper aims to discover the sources of this Prophet’s statement from the authentic source, and to analyse its interpretation based on the opinions of past and contemporary Muslim scholars. It is also to highlight the criticism towards this hadith among the feminists who argue that those Hadiths were interpreted in favour of men’s interest and were influenced by patriarchal culture. Application of qualitative methodology, analytical approach was used to critically analyse the argument around this hadith, while contextual approach was applied to understand its interpretative context. The finding shows that different methods can be applied in understanding the Hadiths with misogynistic content. This is because they could not be interpreted literally, but figuratively and contextually; in order to avoid any misunderstanding against Hadiths concerning women among the community, society and humanities.